The World Bank 2001: vol.1 year in review - The World Bank; The World Bank (Washington: The World Bank, 2001)
This annual report, which covers the period from July 1, 2000, to June 30, 2001, has been prepared by the Executive Directors of both the International Bank for Reconstruction and Development (IBRD) and International Development Association (IDA) in accordance with the respective bylaws of the two institutions
includes index
usc 13/06/17
Ref.
Keywords: Economic assistance; International Finance Corporation